2014
DOI: 10.1111/phn.12162
|View full text |Cite
|
Sign up to set email alerts
|

Mammogram Use and Self‐Efficacy in an Urban Minority Population

Abstract: An association between insurance status and mammogram specific self-efficacy was found. It is likely that mammogram specific self-efficacy will vary with mammogram adherence and insurance status, rather than predict screening. General self-efficacy, higher in screened women, may be an effective mediator through which to develop interventions to increase preventive health-seeking behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 30 publications
(48 reference statements)
2
12
0
Order By: Relevance
“…Self-efficacy refers to the "individual's belief in his or her capacity to execute behaviours necessary to produce specific performance attainments" [33]. In the health context it has been consistently found to have a positive impact in screening attendance for cervical cancer [34], breast cancer [35] and CRC [28,36].…”
Section: Psychological and Factual Variables Involved In The Decisionmentioning
confidence: 99%
“…Self-efficacy refers to the "individual's belief in his or her capacity to execute behaviours necessary to produce specific performance attainments" [33]. In the health context it has been consistently found to have a positive impact in screening attendance for cervical cancer [34], breast cancer [35] and CRC [28,36].…”
Section: Psychological and Factual Variables Involved In The Decisionmentioning
confidence: 99%
“…29,38,39 Furthermore, Tejeda et al 40 found that Hispanic women reported barriers: more often than black women. [41][42][43] Conversely, self-reliance on health seeking 40 However, to our knowledge, it is not clear whether there are differences between women who identify or name potential barriers to timely follow-up and those who are not aware of or refuse to report their barriers.…”
Section: Patient Navigationmentioning
confidence: 99%
“…Although it is difficult to find studies examining such differences in women's ability to identify barriers and actively engage in patient navigation interventions, literature shows that higher patient self-efficacy higher patient self-efficacy has shown to improve cancer screening participation. [41][42][43] Conversely, self-reliance on health seeking and adherence to treatment appear to suggest that individuals who are more self-reliant are less likely to seek help from others, in dealing with treatment for health issues, including mental health problems. [44][45][46] The findings of these studies raise a question regarding how the ability to identify barriers is related to the follow-up of abnormal mammography results among navigated women.…”
Section: Patient Navigationmentioning
confidence: 99%
“…The causes of this disparity in late-stage diagnosis have many origins; however, Latinas’ lower adherence to screening mammography guidelines compared to other races and ethnicities remains a major contributing factor (ACS, 2015). Healthcare factors, such as having health insurance and a usual source of care, appear to be important and may contribute to behavioral disparities (Gonzalez et al, 2012; Jerome-D’Emilia & Suplee, 2015; Nuño, Castle, Harris, Estrada, & Garcia, 2011). The impact of healthcare factors on women’s thoughts about mammograms may underlie these associations, based on psychosocial research concerning conscious thought and behavior (Baumeister, Masicampo, & Vohs, 2011).…”
mentioning
confidence: 99%